Peran Computerized Technical Data and Logistic Support (CLDLS) dalam Mendukung Efektivitas Proyek Development Pesawat Pada PT. Len Industri (Persero) - Asti Istikomah; Firman Yudhanegara (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Aircraft deployment projects involve high complexity due to the integration of multiple divisions, regulatory compliance, and structured technical data management. This study aims to analyze the role of Computerized Technical Data and Logistic Support (CTDLS) in supporting the effectiveness of aircraft deployment projects at PT Len Industri (Persero). This research employed a descriptive qualitative approach using observation, interviews, and documentation during the Internship Program (PKL). The findings indicate that CTDLS plays a strategic role in supporting project planning, organizing, implementation, and controlling processes through systematic management of technical and logistical data. The system manages important documents such as General Configuration System, Work Breakdown Structure (WBS), engineering drawings, and certification documents based on CASR Part 21 and CASR Part 25 regulations. Accurate and well-structured technical data significantly contribute to project timeliness, effectiveness, and operational success. However, several challenges remain, including human error, system limitations, and external factors. Therefore, strengthening digital systems, improving human resource competencies, and optimizing cross-divisional coordination are necessary to enhance the effectiveness of CTDLS implementation.